Image Media to Improve Skills Reading for Elementary School Students - Lestari, Widya; Mahendra, Yasinta; Suprapto, Irawan (Berkala Ilmiah Pendidikan, 2026)
Reading is a fundamental skill at the elementary school level, serving as the foundation for students' intellectual and social progress. However, reality shows that students' reading ability tends to remain low due to the use of unattractive learning models and concentration barriers. This study aims to evaluate the effectiveness of using visual media in improving students' motivation and reading ability, both at the beginning and comprehension levels. The method used was a Systematic Literature Review (SLR) by searching the Google Scholar database between 2021 and 2025. Based on strict inclusion criteria, 10 key articles were selected for further analysis. The results showed an increasing trend in publications regarding visual media, peaking in 2025. Findings from the reviewed articles concluded that the use of visual media, whether in the form of letter cards, series of images, or digital media such as PowerPoint animations, significantly improves students' initial reading ability and comprehension. This visual media can provide concrete representations that help students connect letters with meaningful concepts, while increasing motivation and active participation in learning. Therefore, teacher creativity in integrating visual media with innovative methods is essential to achieve optimal learning outcomes according to the characteristics of elementary school students.